2004
DOI: 10.1021/ja038567d
|View full text |Cite
|
Sign up to set email alerts
|

Hydricities of BzNADH, C5H5Mo(PMe3)(CO)2H, and C5Me5Mo(PMe3)(CO)2H in Acetonitrile

Abstract: The thermodynamic hydride donor abilities of 1-benzyl-1,4-dihydronicotinamide (BzNADH, 59 +/- 2 kcal/mol), C(5)H(5)Mo(PMe(3))(CO)(2)H (55 +/- 3 kcal/mol), and C(5)Me(5)Mo(PMe(3))(CO)(2)H (58 +/- 2 kcal/mol) have been measured in acetonitrile by calorimetric and/or equilibrium methods. The hydride donor abilities of BzNADH and C(5)H(5)Mo(PMe(3))(CO)(2)H differ by 13 and 24 kcal/mol, respectively, from those reported previously for these compounds in acetonitrile. These results require significant revisions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 44 publications
3
106
2
Order By: Relevance
“…155 A key issue in the proposal is that the N-H bond of the adsorbed dihydropyridine is proposed to act as a hydride donor. 92 However, the N-H hydrogen is protic, not hydridic; accordingly, this suggestion is inconsistent with the extensive literature concerning HT from dihydropyridines, 29,40,41,43,76,122,123,125,126,128,152,153 including the present work, which uniformly shows that the hydride transfers from the hydridic hydrogen of the C-H bond and not from N-H. 156 3.8 Recovery of aromaticity drives hydride transfer from PyH2. We have shown that CO2 reduction to CH3OH is accomplished via three successive HTPT steps by PyH2.…”
Section: Figure 4 Analysis Of the Coupled Htpt Process Betweencontrasting
confidence: 90%
See 1 more Smart Citation
“…155 A key issue in the proposal is that the N-H bond of the adsorbed dihydropyridine is proposed to act as a hydride donor. 92 However, the N-H hydrogen is protic, not hydridic; accordingly, this suggestion is inconsistent with the extensive literature concerning HT from dihydropyridines, 29,40,41,43,76,122,123,125,126,128,152,153 including the present work, which uniformly shows that the hydride transfers from the hydridic hydrogen of the C-H bond and not from N-H. 156 3.8 Recovery of aromaticity drives hydride transfer from PyH2. We have shown that CO2 reduction to CH3OH is accomplished via three successive HTPT steps by PyH2.…”
Section: Figure 4 Analysis Of the Coupled Htpt Process Betweencontrasting
confidence: 90%
“…Note that the N scale is a kinetic parameter quantifying the HT rate, whereas the often-employed hydricity is a thermodynamic parameter. [127][128][129] In order to place the N values of PyH2 and Zhou's PhenH2 in perspective relative to established values for dihydropyridines and NaBH4, we calculate activation free energies for HT (∆G ‡ HT) from these donors to CO2 to reduce it to formate (HCOO -) via the Direct-Hydride-Transfer (DHT) model illustrated in Figure 2a.…”
Section: Scheme 5 Reductions Via Direct Hydride Transfers From Relatmentioning
confidence: 99%
“…DuBois and coworkers (11)(12)(13)(14) investigated the thermodynamic hydride-donor abilities (i.e., hydricities) of transition-metal hydrides, formyl complexes, and NADPH-model complexes, such as 1-benzyl-1,4-dihydronicotinamide, in order to develop CO 2 -reduction catalysts in CH 3 CN. The thermodynamic hydricity of a species AH − (or BH) is defined as the standard free energy change for the reaction:…”
Section: Modelmentioning
confidence: 99%
“…15 The sum of reactions (2)- (4) is the heterolytic cleavage of the M-H bond to form H À (reaction (5)) and the associated metal fragment, and the free energy associated with this heterolytic bond cleavage reaction, DG1 H À, is the sum of the free energies for reactions (2)- (4 Using thermodynamic cycles of this type, the hydride donor/acceptor abilities of a large range of compounds have been determined using acetonitrile as the solvent. These include a diverse array of compounds such as NADH analogues (a biological hydride donor), [16][17][18] hydroquinone derivatives, 19 transition metal hydrides of various types, 16,[20][21][22] bridging hydroxides in bimetallic complexes, 23 and aromatic hydrocarbons. 24,25 Of these different classes of compounds, those containing transition metals were of interest because of their ability to bind and activate H 2 to form either dihydrogen or dihydride complexes.…”
Section: Factors Controlling the Thermodynamic Properties Of Transitimentioning
confidence: 99%